Sensor SelComp, a smart component for the industrial sensor cloud of the future - Luís Neto (2017)
Industrial Internet of Thing's will pave the way for Smart Manufacturing initiatives. Intelligence will be notices even in fine grained devices, resulting in complex but at the same time highly efficient manufacturing systems. The typical field worker job will be replaced by machines and human intervention will be shifted to supervision jobs. This work presents Sensor SelComp, a Smart Component which will act in the factory shop-floor, creating the so called digital twin's of machine's by means of sensors and exposing it's functionalities as services. This component is a building block of the SelSus project vision, whose aim is to create and highly effective self-healing production environment. This component eases the process of sensor integration and data analysis by offering runtime reconfiguration and data processing capabilities. Along this document it is shown that Sensor SelComp can cope with tight industrial functional requirements and it's functionalities are described in detail. (c) 2017 IEEE.